On the Nature of Superconducting Precursors in Bi-Pb-Sr-Ca-Cu-O Compositions Fabricated by Hot Shock Wave Consolidation Technology - Chigvinadze, J.; Ashinov, S.; Mamniashvili, G.; Donadze, G.; Peikrishvili, A.; Godibadze, B. (Engineering, Technology & Applied Science Research, 2018)
In this paper, the possibility of critical temperature increasing of superconducting precursor Tс and the current bearing capacity in samples of Bi-Pb-Sr-Ca-Cu-O superconducting system fabricated using hot shock wave consolidation (HSWC) technology and investigated by the vibrating torsional magnetometry method, was studied. The advantage of HSWC technology over the traditional technologies of superconducting composites synthesis is that the high-density materials are made from the Bi-Pb-Sr-Ca-Cu-O superconducting system. After the action of explosive wave the superconductivity is retained. After the explosion a pronounced texture is formed indicating the creation of efficient pinning centers and thus, the increase of current-carrying ability of the obtained material. The critical temperature of potential superconducting precursor Tc of transition to superconducting state increased from Tc=107K for starting sample to Tc=138K, using the HSWC technology for synthesis of samples in range of pressures from P=5GPa up to P=12GPa.